Quantifying Welfare Gains of Increased Trade Integration - Benjamin Jung; Gabriel Felbermayr; Jasmin Gröschl (ZBW - Leibniz-Informationszentrum Wirtschaft, 2018)
Since the 1990s,Germany and other European countries have become more open to trade. The period is characterized by the fall of the iron curtain, the surge of China and its accession to the World Trade Organization (WTO), the introduction of the Euro, the creation of the Schengen area, the enlargement of the European Union (EU), and the Global Europe Initiative. Linking the partial trade effects obtained from our sectoral gravity estimations based on the World-Input-Output Database (WIOD) to real income figures from the Penn World Tables, we find that at least one quarter of the welfare gains realized since 1990 are due to trade policy reforms. Feeding a quantitative simulation exercise based on a version of the Melitz (2003) model with multiple countries and sectors and input-output linkages with the trade costs effects implied by our gravity estimations, we find that Germany's real per capita income would drop by 5.3%, if all trade liberalization steps since 1990were fully undone.
Keywords: F12; F15; 330; NewQuantitative TradeModels; Gravity equation; European Integration; Gains from Trade